Rapid detection of listeria monocytogenes in food by polymerase chain reaction - Ennaji, H; Timinouni, M; Ennaji, M M; Ait M‘hand, R; Hassar, M; Cohen, N (Cellular and Molecular Biology, 2009)
The standard conventional methods for the detection of Listeria monocytogenes in foods require high time 7 to 10 days to give ready results. To dissolve this problem we have evaluate a short method using Polymerase Chain Reaction (PCR) to analyze food samples. In parallel with this study, a comparison was made between PCR amplification from templates directly prepared from food and the official standard ISO procedure 11290-1. In this study we have used a Half Frazer broth as an enrichment medium; there were positive results of PCR detection of L. monocytogenes in different food sample analyzed (milk, cheese and meat) with approximately 1.5 101 Colony Forming Units /25g in less than 36 h. This PCR procedure has proved to be rapid and sensitive method suitable for the routine analysis; firstly, because this assay required just a short pre-enrichment step before PCR. Secondly, this procedure is very simple and time-saving; it could take less than one working day to obtain results if initial microbiological load was very important.